Strategi Humas KPU Bea dan Cukai Tipe A Tanjung Priok dalam Mengelola Media Sosial Instagram - Belinda Nathania; Daniel Tamburian (Kiwari, 2022)
Public Relations is an important part for organizations or companies, because the activities carried out by PR practitioners aim to build and maintain the company's brand image so that it remains good in the eyes of the community. In providing understanding to the community, there must be a party who has the responsibility for providing the information, which connects the community with the public. Those parties are none other than public relations or public relations practitioners. Along with the awareness that public relations plays an important role in building the image of the organization, the presence of public relations in Customs and Excise is also felt as a necessity that must be prioritized. Public Relations of Customs and Excise continues to play a role in strengthening relations with the community through the implementation of policy socialization related to customs and excise. To communicate with the public, Customs and Excise's public relations are also closer to each other through the media, either through advertisements, social media, or by providing information on the latest customs developments. The theory used in this research is public relations theory, public relations strategy, and social media. This research uses descriptive qualitative research methods by collecting data in the form of interviews, documentation, and observations. Humas merupakan bagian penting bagi organisasi ataupun perusahaan, karena kegiatan yang dilakukan oleh praktisi Humas bertujuan untuk membangun serta menjaga brand image perusahaan agar tetap baik dimata masyarakat. Dalam memberikan pemahaman kepada masyarakat, harus ada pihak yang memiliki tanggung jawab atas pemberian informasi tersebut, yang menghubungkan antara masyarakat dengan publiknya. Pihak tersebut tidak lain tidak bukan adalah praktisi public relations atau humas. Seiring dengan kesadaran bahwa humas memegang peranan yang penting dalam membangun citra organisasi, keberadaan humas di Bea Cukai juga dirasakan sebagai suatu kebutuhan yang harus diutamakan. Public Relations Bea Cukai berperan terus mempererat hubungan dengan masyarakat melalui pelaksanaan sosialisasi-sosialisasi kebijakan yang berkaitan dengan kepabeanan dan cukai. Untuk berkomunikasi dengan publiknya, public relations Bea Cukai juga mendekatkan diri melalui media, baik melalui iklan, media sosial, ataupun dengan menyediakan informasi mengenai perkembangan bea cukai terbaru. Teori yang digunakan dalam penelitian ini adalah teori humas/Public Relations, strategi humas, dan media sosial. Peneltian ini menggunakan metode penelitian deskripsif kualitatif dengan mengumpulkan data berupa wawancara, dokumentasi, dan observasi.